Construction Of Recombinant Escherichia Coli Bad85 For The Production Of High Purity L-Lactic Acid - Tengku Zainal Mulok, Tengku Elida (2008)
Lactate dehydrogenase (LDH, EC 1.1.1.27) catalyzes the oxidation of pyruvate to lactate in facultative anaerobes. Two forms of lactate dehydrogenase with different substrate specificities have been identified namely the L-lactate dehydrogenase (EC 1.1.1.27) and D-lactate dehydrogenase (EC 1.1.1.28). The L-lactate dehydrogenase is involved in the reduction of pyruvate into L-lactic acid whilst the D-lactate dehydrogenase is responsible for the formation of D-lactic acid. L-lactic acid is more preferable to D-lactic acid in the production of bioplastics since it is metabolizable in human and animals. The objective of this study is to isolate and clone the L-lactate dehydrogenase (L-ldh) gene from Enterococcus faecalis KK1 and express in Escherichia coli SZ85 for the production of L-lactic acid. E. coli SZ85 strain has five chromosomal deletions (pflB, ackA, adhE, ldhA, and frdBC), namely D-lactate dehydrogenase, pyruvate formate lyase, acetate kinase, alcohol/aldehyde dehydrogenase and fumarate reductase and a chromosomally integrated L-ldh gene from Pediococcus acidilactici. The 954 bp gene was isolated by using the polymerase chain reaction (PCR). Primers EF.f (forward) and EF.r (reverse) were designed based on published gene sequence of L-ldh, and the PCR amplified L-ldh gene was cloned into TOPO TA cloning vector. The DNA sequencing results revealed 99% homology with published sequence in the database. The gene was subcloned into E. coli expression vector (pBAD) using the restriction enzymes Eco R1 and Xho 1. The pBAD-ldh gene was later transformed into E. coli SZ85 using electroporation. Sodium dodecyl sulfide-polyacrylamide gel electrophoresis (SDS-PAGE) analyses indicated that L-lactate dehydrogenase recombinant protein was successfully expressed in E. coli SZ85 with the expected size of 40 kDa. Western blot analysis revealed an immunoreactive band at 40 kDa size which further confirmed the expression of L-ldh gene. In this study, the mouse monoclonal antibody acted as the primary antibody and horse radish peroxidase (HRP), conjugated to the secondary antibody (anti-goat antibody) was used as a probe to confirm the recombinant protein. The recombinant E. coli BAD85 underwent fermentation using shake flasks to establish the optimum pH and temperature conditions for lactic acid production from fructose and was conducted at pH between 5.0–7.0 and temperature 30-37ºC. The best condition was later selected to.investigate the effect of temperature and pH on the production of lactic acid using E. coli BAD85 in a 2-L bioreactor system. Batch cultivations in 2-L stirred tank fermenter were carried out using the conditions determined during shake flask fermentation to further improve L-lactic acid production by recombinant E. coli BAD85. Cultivation of E. coli BAD85 at pH 7.0 and incubation temperature of 37ºC was found to be the best condition for producing L-lactic acid. These conditions were able to produce 7.04 gL-1 L-lactic acid with a high purity of 98%, 0.70 gg-1 yield and productivity of 0.029 gg-1 h-1. The recombinant was able to achieve a 98% plasmid stability indicating that the cells were fairly stable for fermentation process.